2017
DOI: 10.3389/fneur.2017.00582
|View full text |Cite
|
Sign up to set email alerts
|

Manual Dexterity and Intralimb Coordination Assessment to Distinguish Different Levels of Impairment in Boccia Players with Cerebral Palsy

Abstract: BackgroundBoccia is a paralympic sport played by athletes with severe neurological impairments affecting all four limbs. Impaired manual dexterity (MD) and intralimb coordination (ILC) may limit individuals’ ability to perform certain activities such as grasping, releasing, or manipulating objects, which are essential tasks for daily life or to participate in para sports such as boccia. However, there are currently no specific instruments available to assess hand–arm coordination in boccia players with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
16
0
2
Order By: Relevance
“…4 Research has provided some understanding of how these clinical features impact on sport and exercise performance, [5][6][7] with performance deficits being attributed to losses in strength, 8 9 joint range of motion 10 and motor coordination. 11 Motor coordination, which is defined as the ability to produce skilled movement fluidly, rapidly and accurately is affected in Para athletes with brain injury. 4 10 It is yet to be reported how swim performance is affected by motor coordination impairment.…”
Section: Introductionmentioning
confidence: 99%
“…4 Research has provided some understanding of how these clinical features impact on sport and exercise performance, [5][6][7] with performance deficits being attributed to losses in strength, 8 9 joint range of motion 10 and motor coordination. 11 Motor coordination, which is defined as the ability to produce skilled movement fluidly, rapidly and accurately is affected in Para athletes with brain injury. 4 10 It is yet to be reported how swim performance is affected by motor coordination impairment.…”
Section: Introductionmentioning
confidence: 99%
“…These results can be construed from different perspectives. On the one hand, the allocation of a sport class in Boccia is not based solely on players´trunk function, as there are other factors to consider, such as arm function or manual dexterity [21], that usually have greater importance for the classifiers for decision-making due to the high impact on performance (i.e., ball throwing). This rationale would be supported by the fact that dynamic posturographic tasks were also unable to discriminate between BC1 and BC2 classes.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to develop a clear structure based on evidence on how to classify these athletes. Inspiration for research strategies can be found in published studies measuring coordination in other parasports such as athletics and boccia (Connick et al, 2016;Roldan et al, 2017).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%